Apparent Digestibility Coefficients of Peruvian Fish Meal and Yellow Corn by Colossoma macropomum (Actinopterygii, Characidae) - Walter Gutierrez, Felix (2008)
The apparent digestibility coefficients (ADC) of dry matter (DM), crude protein (CP) crude lipids (CL) and gross energy (GE) in the food ingredients Peruvian fish meal (PFM) and Yellow Corn (YC) were obtained with juveniles of Colossoma macropomum (150,0 ± 25,5 g). In the experiments the reference diet was mixed with test ingredients in a ratio of 70:30 to produce two test diets. The Chromic Oxide (Cr2O3) was use as the inert indicator. The reference diet and the test diets were fed to C. macropomum reared at 27 ºC. Dissolved oxygen was 7 mg/L and pH was 7,5. The fecal samples were collected by siphoning. The ADC to DM, CP, CL and GE in the PFM were of 88,06 ± 0,83%, 87,08 ± 1,34%, 85,87 ± 2,69 y 87,29 ± 1,57% respectively. The ADC to DM, CP, CL and GE in the yellow corn were of 82,38 ± 1,02%, 75,46 ± 1,53%, 76,17 ± 2,43% y 75,04 ± 1,80% respectively. The apparent digestible energy to the HPP and MAD were 3950 Kcal/kg and 2830 kcal/kg respectively. It was concluded that C. macropomum has used more efficiently the protein and energetic fractions from PFM. At the same time C. macropomum shows ability to use efficiently the energetic fraction from soluble carbohydrates of YC.